2017
DOI: 10.3390/app7060605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seasonal Temperature on the Performance and on the Microbial Community of a Novel AWFR for Decentralized Domestic Wastewater Pretreatment

Abstract: Due to environmental burden and human health risks in developing countries, the treatment of decentralized domestic wastewater has been a matter of great concern in recent years. A novel pilot-scale three-stage anaerobic wool-felt filter reactor (AWFR) was designed to treat real decentralized domestic wastewater at seasonal temperature variations of 8 to 35 • C for 364 days. The results showed that the average chemical oxygen demand (COD) removal efficiencies of AWFR in summer and winter were 76 ± 7.2% and 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…As far as biogas production is concerned, Pentassuglia et al (2020) highlighted a clear correlation between biogas yield and operating temperature of the plant (Figure 4.2). This finding is in agreement with other studies reporting that low temperatures led to a reduction in biogas production, even due to an increase in methane solubility in liquid phase (Bandara et al, 2012;Li & Lu, 2017). According to the biogas production measured, the methane yield ranged 104-267 NmLCH 4 /gCOD removed when the AnSBio operate at the lowest and the highest temperature, 14°C and 35°C, respectively.…”
Section: Case Study: Anaerobic Sequencing Biofilter (Ansbio)supporting
confidence: 92%
See 4 more Smart Citations
“…As far as biogas production is concerned, Pentassuglia et al (2020) highlighted a clear correlation between biogas yield and operating temperature of the plant (Figure 4.2). This finding is in agreement with other studies reporting that low temperatures led to a reduction in biogas production, even due to an increase in methane solubility in liquid phase (Bandara et al, 2012;Li & Lu, 2017). According to the biogas production measured, the methane yield ranged 104-267 NmLCH 4 /gCOD removed when the AnSBio operate at the lowest and the highest temperature, 14°C and 35°C, respectively.…”
Section: Case Study: Anaerobic Sequencing Biofilter (Ansbio)supporting
confidence: 92%
“…As for example, similar results were obtained by Bodík et al (2002), evaluating the performances of an UAF in the temperature range 8-23°C, which found 84-87% COD removal when operating the plant at 15°C. Lower COD removal was obtained by other authors with different biofilters: Li and Lu (2017) reported only a 52 ± 6% COD removal when operating an anaerobic wool-felt filter reactors (AWFRs) during winter (10°C ± 2) at a 3-d HRT. The COD removal efficiency approached 60% when operating temperature was increased to 21°C (spring).…”
Section: Case Study: Anaerobic Sequencing Biofilter (Ansbio)mentioning
confidence: 75%
See 3 more Smart Citations